2021
DOI: 10.1053/j.gastro.2021.05.047
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Trial Comparing the Specific Carbohydrate Diet to a Mediterranean Diet in Adults With Crohn’s Disease

Abstract: Crohn's disease symptomaƟc remission Fecal calprotecƟn response CRP response Week 6 Outcomes Specific Carbohydrate Diet Mediterranean Diet Participants achieving outcome (%) See Covering the Cover synopsis on page 739; See editorial on page 798. BACKGROUND & AIMS: This study compared the effectiveness of the Specific Carbohydrate Diet (SCD) to the Mediterranean diet (MD) as treatment for Crohn's disease (CD) with mild to moderate symptoms. METHODS: Adult patients with CD and with mild-to-moderate symptoms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
130
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 42 publications
4
130
1
Order By: Relevance
“…In adults with CD, a recent randomized trial that included interventions with either the SCD or the Mediterranean diet has also demonstrated a remarkable effect of diet in inducing remission. 23 Specifically, after only 6 weeks on either diet half of the patients in the trial achieved symptomatic remission with ≥30% showing reduction of fecal calprotectin levels. 23 For ulcerative colitis (UC), a catered nutritious low-fat/high-fiber diet has been shown to improve the overall quality of life, lower inflammatory markers, decreased dysbiosis, and specifically favor Faecalibacterium prausnitzi .…”
Section: Introductionmentioning
confidence: 97%
“…In adults with CD, a recent randomized trial that included interventions with either the SCD or the Mediterranean diet has also demonstrated a remarkable effect of diet in inducing remission. 23 Specifically, after only 6 weeks on either diet half of the patients in the trial achieved symptomatic remission with ≥30% showing reduction of fecal calprotectin levels. 23 For ulcerative colitis (UC), a catered nutritious low-fat/high-fiber diet has been shown to improve the overall quality of life, lower inflammatory markers, decreased dysbiosis, and specifically favor Faecalibacterium prausnitzi .…”
Section: Introductionmentioning
confidence: 97%
“…EEN is recommended as first-line therapy to induce remission in paediatric CD [ 42 ]. While these recommendations differ in adult CD management [ 2 , 60 ], a prospective, open-label trial from 2018 in Japan assessing the role of combination infliximab dose escalation with elemental diet versus infliximab dose escalation alone had to be stopped early due to clear benefits in the combination therapy over monotherapy treatment group in the midterm analysis [ 61 ].…”
Section: Diets With Proof Of Clinical Efficacy For Ibdmentioning
confidence: 99%
“…Preliminary studies of SCD intervention in pediatric and adult IBD patients have demonstrated promising results in low-number patient cohorts, including achieving clinical and mucosal remission and normalization of blood and stool laboratory markers [8][9][10][11][12][13][14]. A recent randomized trial in adult Crohn's disease patients demonstrated symptomatic remission and fecal calprotectin (FCP) response in 46.5% and 34.6% of patients, respectively, after a six-week regimented SCD intervention, matching the response seen in the Mediterranean diet intervention arm [15].…”
Section: Introductionmentioning
confidence: 96%